2020
DOI: 10.3390/su12114588
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a Sustainable Cropping System in the North China Plain Using a Modelling Approach

Abstract: The North China Plain (NCP) is one of the most important grain production regions in China. However, it currently experiences water shortage, severe nonpoint source pollution, and low water and N use efficiencies (WUE and NUE). To explore sustainable agricultural development in this region, a field experiment with different cropping systems was conducted in suburban Beijing. These cropping systems included a winter wheat and summer maize rotation system for one year (WM), three harvests (winter wheat-summer ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Additionally, the WUE of 2H1Y reached 1.33 kg m −3 , while the WUE amounts of the other systems were around 1 kg m −3 . Wang et al [ 2 ] reported that the WUE under the 1H1Y system was higher than the WUEs of 3H2Y and 2H1Y because this pattern had a lower ET. In this study, 2H1Y_RI had the highest WUE.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, the WUE of 2H1Y reached 1.33 kg m −3 , while the WUE amounts of the other systems were around 1 kg m −3 . Wang et al [ 2 ] reported that the WUE under the 1H1Y system was higher than the WUEs of 3H2Y and 2H1Y because this pattern had a lower ET. In this study, 2H1Y_RI had the highest WUE.…”
Section: Discussionmentioning
confidence: 99%
“…The North China Plain (NCP), an area of approximately 32 million ha and 17.98 million ha of agricultural land, is one of the most important grain production regions and one of the main irrigated regions in China. In order to make full use of light and heat resources and achieve a high grain production, the intensive winter wheat–summer maize (WW-SUM) double cropping system with two harvests in one year (2H1Y) has been adopted widely in this region [ 1 , 2 ]. Although this cropping system has significantly enhanced grain production, it has also brought severe issues such as groundwater depletion and environmental pollution [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations